Upaya Kepala Sekolah Dalam Meningkatkan Mutu Kegiatan Belajar Mengajar di SMP Negeri 1 Rongkop Gunungkidul Tahun Pelajaran 2022/2023 - Eka Puji Srilestari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Education in Indonesia until now, is still running slowly, like an old car running in the middle of traffic flow and on the highway, because education in Indonesia is still plagued by very big problems about the quality of education that is still low. The quality of education is the quality of a teacher, either his understanding or ability to interact with teaching and learning, whose indicators can be seen from the results of student learning achievement. There are several factors that affect the improvement of KBM quality. Based on the problems and research objectives stated above, this study seeks to obtain complete and in-depth information about the principal's efforts in improving the quality of KBM. This research uses a type of research with a qualitative approach. As Zuchri states, qualitative research is naturalistic research. The conclusions that can be drawn from the Principal's Efforts in Improving the Quality of Teaching and Learning Activities (KBM) are as follows: The principal of SMP Negeri 1 Rongkop always strives to improve the Quality of KBM, with efforts such as : 1. Always strive for teachers according to their respective competencies. 2. Always hold or attend training on the ability to manage KBM. 3. Always provide coaching/motivation to students. 4. Always strive for adequate learning infrastructure 5. Always supervise the running of KBM.